Modeling and analyzing for network coded TCP - San-feng ZHANG; Shuang LI; Xiang LAN; Yong-dong HU (Tongxin xuebao)
The evolutionary process of network coded TCP against lossy links and error correcting coding were analyzed. Ignoring the slow start phase, the state transition process of congestion window and available window was described based on a three-dimension Markov chain model. With maximum window size, end-to-end packet loss rate and redun-dancy factor as input parameters, throughput of network coded TCP was calculated to carry quantitative analysis of fac-tors affecting the network coded TCP performance in the numerical analysis model. Simulation results based on the NS2 simulator show that the numerical analysis model achieves fairly high accuracy.